Eating disorders: etiologies, triggering factors, management challenges, and screening methods - Figueiredo, Bárbara Queiroz de (2022)
The ideals of body and health instituted by society were not always the same. New stereotypes make the current aesthetic standard different from that established at the beginning of the 20th century. Currently, the overvaluation of a thin body, by a large part of the population, is seen as a sign of health, and can thus create a situation of frustration, low self-esteem and discrimination among those who do not fit this rule. In view of these facts, the problem of eating disorders arises, which are psychiatric disorders of multifactorial etiology, characterized by extremely distorted consumption, eating patterns and attitudes and exaggerated concern with weight and body shape, in which multidisciplinary investigations carried out in different contexts, show that part of its etiology remains unknown. eating disorders can be characterized by behavioral disturbances related to eating habits. Generally, they involve an excessive concern with body image, generating behaviors such as reduced food intake, use of laxatives and diuretics, or inducing vomiting soon after consumption of food. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), the eating disorders are part of the group of eating disorders: Pica, Rumination Disorder, Restrictive/Avoidant Eating Disorder, Anorexia Nervosa, Bulimia Nervosa, and Compulsion Disorder. Feed.